Nonlinear formation control of marine craft - Skjetne, R.; Moi, S.; Fossen, T.I. (Proceedings of the 41st IEEE Conference on Decision and Control, 2002, 2002)
This paper investigates formation control of a fleet of ships. The control objective for each ship is to maintain its position in the formation while a (virtual) Formation Reference Point (FRP) tracks a predefined path. This is obtained by using vectorial backstepping to solve two subproblems; a geometric task, and a dynamic task. The former guarantees that the FRP, and thus the formation, tracks the path, while the latter ensures accurate speed control along the path. A dynamic guidance system with feedback from the states of all ships ensures that all ships have the same priority (no leader) when moving along the path. Lyapunov stability is proven and robustness to input saturation is demonstrated using computer simulations.